Optimizing Red Tilapia Juvenile (Oreochromis niloticus) Nursery in Recirculating Aquaculture with Ultrafine Bubbles System at Variable Stocking Densities - Subhan, Ujang; Meisani, Isni; Afriza, Azka Reyza; Nuruhwati, Isni; Grandiosa, Roffi; Al Mujahid, Muhammad Abdul Aziz (Jurnal Perikanan Universitas Gadjah Mada, 2025)
The increased demand for red tilapia (Oreochromis niloticus) production requires a sufficient supply of high-quality juveniles. Technological innovation is crucial for developing quantifiable, highly productive, efficient, environmentally sustainable, and ecologically sound juvenile production systems. This study aimed to analyse the effect of high stocking density on the growth performance of red tilapia juveniles cultured using ultrafine bubble technology in a recirculating aquaculture system (UFBs-RAS). A completely randomised experimental design was used with four stocking density treatments: one control treatment (4 fish/L with aeration) and three treatments under the UFBs-RAS system at 4, 6, and 8 fish/L densities. Each treatment was replicated four times. The juvenile red tilapia used in this study had an average initial total length of 4.34 ± 0.23 cm and a weight of 1.47 ± 0.31 g. They were obtained from fishpond research at the FINDER UCoE Experimental Station, Universitas Padjadjaran. The findings indicated that UFBs-RAS facilitated optimal production performance, even at the maximum stocking density of 8 fish per liter. The performance metrics comprised a survival rate of 98.75%, a specific growth rate in weight of 4.93 ± 0.062%/d, a specific growth rate in length of 3.88 ± 0.05%/d, a protein efficiency ratio of 2.48 ± 0.02, a feed conversion efficiency of 96.5 ± 0.58%, and a coefficient of variation of 33.7 ± 1.2%. These data validate that incorporating UFBs-RAS is a viable and efficient method to improve the quality and productivity of red tilapia juveniles.